The Teaching and Learning of Arabic in Early Modern Europe - Loop, Jan; Hamilton , Alastair; Burnett, Charles (The History of Oriental Studies, 2017)
The essays in this volume shed light on how, for what purposes and to what extent the Arabic language was taught and studied by European scholars, theologian, merchants, diplomats and prisoners in early modern Europe.